Efficient degradation of naproxen in a three dimensional biofilm electrode magnetism reactor (3DBEMR): Removal performance and microbial community. (February 2022) - Li, Zichen; Feng, Yan; Chang, Lei; Long, Yingying; Suo, Ning; Wang, Zhongwei; Yu, Yanzhen
Graphical abstract: Highlights: A three-dimensional biofilm electrode magnetism reactor (3DBEMR) was established. Removal rate of naproxen was enhanced greatly by 3DBEMR. Electric field played a important role for naproxen degradation in 3DBEMR. Magnetic field played a strengthening or assisting role in 3DBEMR. Biological community was changed because of the electro-magnetic superposition. Abstract: A three-dimensional biofilm electrode magnetism reactor (3DBEMR) was constructed to removal naproxen (NPX). This study evaluated 3DBEMR performance in removal of refractory NPX, while also discussing the effect of the electro-magnetic superposition on microbial community by high throughput sequencing. Results indicated that 3DBEMR's average removal rate for NPX stood at 88.36%, representing an increase by 75.24%, 65.03% and 12.36%, respectively, compared to 3DBR (Three-Dimensional Biofilm Reactor), 3DBMR (Three-Dimensional Biofilm Magnetism Reactor) and 3DBER (Three-Dimensional Biofilm Electrode Reactor). This was attributed to the influence of electro-magnetic adsorption, electro-oxidaton/catalysis, and electro-magnetic biodegradation. Another major contributing factor to NPX removal was the presence in 3DBEMR of high-abundance genera such as Rhodobacter, Porphyrobacter, Methyloversatilis, Sphingopyxis, Bosea, Singulisphaera, Sphingomonas . Therefore, the 3DBEMR was successfully demonstrated to be a flexible and effective technique in NPX degradation, which would help to better understand the effect of superposition of electric and magnetic fields on microbial community.